ANALISIS FORMALISTIK, EKSPRESIVISTIK, DAN INSTRUMENTALISTIK PADA POSTER SERIAL FILM LAYANGAN PUTUS - Martinus Eko Prasetyo; Yana Erlyana; Asrullah Ahmad (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
The drama series Layangan Putus, which has recently become the general public's talk, is quite popular and watched by many people. Interestingly, there are many funny memes about the news about the film series Layangan Putus on social media. Besides that, many early semester VCD students at Bunda Mulia University need clarification every time they make a poster design because of difficulties in determining the poster layout. Therefore, the author tries to research the main visual of the posters from the Layangan Putus film series by using a scientific approach to Visual Communication Design; the author discusses film posters using a formalistic, expressive, and instrumentalistic approach in terms of visual elements, layout, and colour. The aim is to show the meaning of the poster for the Serial Film Layangan Putus in a formalistic, expressive, and instrumentalistic manner using a qualitative descriptive method to describe as wide as possible the information being analysed. Practically, this study concludes the results of the application of design principles and the primary visual elements, which are very influential in making the aesthetics of a film poster layout more attractive. Keywords: poster, movie series, layangan putus